Management of benign stenoses of the large airways in the university hospital in Prague, Czech Republic, in 1998-2003 - Marel, Miloslav; Pekarek, Zdenek; Spasova, Irena; Pafko, Pavel; Schutzner, Jan; Betka, Jan; Pospisil, Ronald (Respiration; international review of thoracic diseases, 2005)
BACKGROUND: Clinically significant benign stenoses of the large airways develop in about 1% of patients after intubation. The management of benign stenoses is not unified around the world, nor are there any accepted methods for their screening. OBJECTIVES: The purpose of this study is to describe and compare results of interventional bronchoscopy and surgical therapy of benign stenoses as well as to propose an algorithm for the management of this airways disorder. METHODS: Prospective study on 80 consecutive patients with benign stenoses of the large airways admitted to the Pulmonary Department of the University Hospital of Prague-Motol. RESULTS: Sixty-two patients developed stenoses after endotracheal intubation or tracheostomy, in 18 patients the stenosis was caused by other diseases or pathological situations. Thirty-eight patients were sent for surgical resection of the stenotic part of the airways. 2 surgically treated patients developed recurrence of the stenosis and had to be reoperated on. Narrowing of the trachea at the site of end-to-end anastomosis developed in 6 other patients and was cured by interventional bronchoscopy. The remaining 42 patients were treated by interventional bronchoscopy (Nd-YAG laser, electrocautery, stent) which was curative in 35 patients. Sixty-five patients were alive at the time of evaluation, 15 patients died. Five of them died between 3 and 14 (median 4) months after surgery from a disease other than airway stenosis. Ten nonresected patients also died, with 1 exception, due to a disease other than airway stenosis; the median survival was 9 months. CONCLUSIONS: We recommend to assess the patient for surgery after the initial diagnosis and therapeutic bronchoscopy with dilatation of the stenosis. If the patient is not a suitable candidate for resection, interventional bronchoscopy is an appropriate alternative for the management of benign stenoses of the large airways.
Keywords: senioři; Constriction, Pathologic; stenóza; Intubation, Intratracheal; tracheostomie; mladiství; Česká republika; bronchoskopie; nemocnice univerzitní; Middle Aged; mužské pohlaví; Tracheostomy; bronchiální nemoci; Prospective Studies; Adult; intratracheální intubace; Czech Republic; Tracheal Stenosis; ženské pohlaví; Humans; prospektivní studie; Bronchial Diseases; Bronchoscopy; stenóza průdušnice; lidé středního věku; dospělí; Female; Aged; Hospitals, University; Adolescent; lidé; Male